1909 թ. կոտորածները եւ Մեծի Տանն Կիլիկիոյ Կաթողիկոսութիւնը - Յարութիւնեան, Վահագն (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В статье рассматриваются исторические события конца 19-го и начала 20-го вв., с помощью которых описывается общая политико-экономическая ситуация в Армянской Киликии, где в начале 1909 года турецкое правительство организовало массовую резню армянского населения. Опираясь на архивные материалы, а так же используя сведения периодической печати того времени и свидетельства очевидцев, автор составляет по возможности всеобъемлющий образ драматических событий, свои выводы и заключения, сопоставляя с общепринятыми научными подходами по данному вопросу. The article examines the historical events of the late 19th and early 20th centuries, which helped to restore the general political and economic situation in Armenian Cilicia, where at the beginning of 1909 the Turkish government organized the massacre of the Armenian population. Based on archive materials, as well as using information from periodicals of that period and eyewitness accounts, the author draws up a comprehensive image of those dramatic events making his own conclusions in accordance with scientifically accepted approaches on this issue.
Keywords: History